Ostracodes não-marinhos da Formação Orós, Cretáceo Inferior da Bacia do Iguatu: taxonomia e inferências bioestratigráficas e paleoambientais - Santos Filho, Marcos Antonio Batista dos (Universidade do Vale do Rio dos Sinos, 2020)
The Interior Northeast Basins of Brazil are a group of basins situated to the south of the Potiguar Basin that originated during the rifting that led to the establishment of the Atlantic Ocean, and can be used as analogues to the depositional environments of the continental margin. However, many of these basins were not comprehensively studied, even though they have an important record of the Lower Cretaceous, with an extensive fossiliferous content. Non-marine ostracods, an important group for the biostratigraphy and correlation between Lower Cretaceous Brazilian basins, are abundant in the region. The objective of this thesis is to study the ostracod fauna of two continuous sections in the Iguatu Basin, named Transnordestina A and Transnordestina B, in order to contribute to the biostratigraphic and paleoenvironmental knowledge of this group for the region. 156 samples were collected, in which 19 species from genera were found: Cypridea hystricoides, C. paraibensis, C. cf. C. clavata, C. punctacentralis sp. nov., Brasacypris ovum, Pattersoncypris sinuata, P. cf. P. sinuata, Pattersoncypris? sp., Ilyocypris? arca., Ilyocypris? latanodi., Rhinocypris? ericius, Pythagoracypris latavectis, Hastacypris adamantem, Looneyellopsis mvili, Musacchiocythere plastica, Musacchiocythere? sp., Alicenula leguminella, A. cf. D. oblonga, and an incerta sedis species. Based on the species found, a Hauterivian – Aptian age interval was inferred. For the paleoenvironmental interpretation, two main ostracod groups were found: one dominated by Alicenula, indicative of higher humidity periods, and one dominated by Cypridea¸ indicating dryer periods. High values of the elemental ratios Ca/Ti and Ca/ΣTi, Fe, Al indicated that arid conditions dominated at the base of the sections. Ciclostratigraphic analysis indicated the presence of six 120 ka cycles for the base of the section and 10 120 ka and three 405 ka for the middle and top. The author hopes that this work demonstrates the potential that the deposits of the small Northeastern basins have to help advancing the biostratigraphic and paleoenvironmental knowledge for the Lower Cretaceous, which still requires greater amount of date for its better understanding.
Keywords: Ostracodes não-marinhos; Paleolimnologia; Bacias interiores do Nordeste Brasileiro; Non-marine ostracods; Paleolimnology; Interior Northeastern Brasilian basins; ACCNPQ::Ciências Exatas e da Terra::Geologia